Effect of electromagnetic interference shield on package and PCB - Kim, Moonjung (International Journal of Engineering and Technology, 2019)
In this work, the effect of metal shield of ball grid array package on electromagnetic coupling is analysed. To compare the electromagnetic coupling between the packages on a printed circuit board, two test vehicles are presented. All vehicles have a metal shield overall surface of their package with the exception of their bottom side. One vehicle connects the metal shield to the ground plane. However, the other does not connect between those. Electromagnetic coupling simulations for two test vehicles are performed with frequency range from 10 MHz to 15 GHz. Electrical field distributions of the test vehicles are also calculated. From the calculation results, the metal shield structure in this work can reduce effectively the electromagnetic coupling between the packages from the frequency range of 11 GHz to 15 GHz. Connecting the metal shield on the package to the ground plane provides better electromagnetic interference between the packages.
Keywords: Electromagnetic Interference; Coupling; Metal Shield; Package; S-Parameter.